Expression of a renal type I sodium/phosphate transporter (NaPi-1) induces a conductance in Xenopus oocytes permeable for organic and inorganic anions. - Busch, A E (1996)
Two distinct molecular types (I and II) of renal proximal tubular brush border Na+/Pi cotransporters have been identified by expression cloning on the basis of their capacity to induce Na+-dependent Pi influx in tracer experiments. Whereas the type II transporters (e.g., NaPi-2 and NaPi-3) resemble well known characteristics of brush border Na+/Pi cotransport, little is known about the properties of the type I transporter (NaPi-1). In contrast to type II, type I transporters produced electrogenic transport only at high extracellular Pi concentrations (> or =3 mM). On the other hand, expression of NaPi-1 induced a Cl- conductance in Xenopus laevis oocytes, which was inhibited by Cl- channel blockers [5-nitro-2-(3-phenylpropylamino)benzoic acid (NPPB) > niflumic acid >> 4,4'-diisothiocyanatostilbene-2,2'-disulfonic acid]. Further, the Cl- conductance was inhibited by the organic anions phenol red, benzylpenicillin (penicillin G), and probenecid. These organic anions induced outwardly directed currents in the absence of Cl-. In tracer studies, we observed uptake of benzylpenicillin with a Km of 0.22 mM; benzylpenicillin uptake was inhibited by NPPB and niflumic acid. These findings suggest that the type I Na+/Pi cotransporter functions also as a novel type of anion channel permeable not only for Cl- but also for organic anions. Such an apical anion channel could serve an important role in the transport of Cl- and the excretion of anionic xenobiotics.